A Dosimetric Analysis of Preoperative Intensity-modulated and Image-guided Radiation Therapy with and without Simultaneous Integrated Boost for Locally Advanced Rectal Cancer. (October 2015) - Yang, Yongqiang; Feng, Linchun; Wang, Yunlai; Ge, Ruigang; Gong, Hanshun; Xie, Chuanbin; Wang, Jinyuan; Chen, Jing; Lan, Yuling; Ma, Lin
Preoperative concurrent chemoradiation, total mesorectal excision and adjuvant chemotherapy have become the standard of care for patients with locally advanced rectal cancer (LARC). Several studies have reported increased pathologic complete response rates and improved locoregional control with escalating doses of preoperative radiotherapy. In this study, we assess the dosimetric feasibility and impact of intensity-modulated and image-guided radiation therapy (IMRT-IGRT) with a simultaneous integrated boost (SIB) in preoperative chemoradiation for LARC. Ten rectal cancer patients treated with preoperative chemoradiation were enrolled in this study, and IMRT56.25Gy and IMRT50Gy plans were made for each patient with a CTV-PTV50Gy margin of 5 mm and a GTV-PTV56.25Gy margin of 10 mm adapted to daily KV cone-beam computed tomography (CBCT) imaging. In the boost group (IMRT56.25Gy), the prescribed doses were 56.25 Gy to the gross tumor (PTV56.25Gy) and 50 Gy to areas at high risk of harboring microscopic disease (PTV50Gy). Doses were delivered over 25 daily fractions using a SIB technique. In the no-boost group (IMRT50Gy), the prescribed dose was 50 Gy to PTV50Gy without a boost. The goals were to give at least 95% of the prescribed doses to at least 95% of the PTVs while keeping irradiated volumes of the organs at risk dose as low as possible. Differences in dose distributions between the two sets of plans were analyzed using a paired sample t -test. All IMRT56.25Gy plans met the needs of the prescribed doses and organ at risk dose constraints. Compared to IMRT50Gy, the addition of a SIB in IMRT56.25Gy resulted in significant increases in mean dose and V40Gy to the bladder and significant increases of V30Gy and V40Gy to femoral heads ( p < 0.05 for all points). There were no significant differences in dose to small bowel or pelvic bone marrow between the two sets of plans. Preoperative IMRT-IGRT with SIB for LARC is feasible dosimetrically with respect to organ at risk dose constraints. A phase II trial to evaluate the clinical safety and efficacy of this approach is being undertaken.